2017
DOI: 10.1002/jbio.201700157
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects of Er:YAG laser irradiation on the proliferation of primary human gingival fibroblasts

Abstract: We investigated the biological effects of Er:YAG laser (2940-nm; DELight, HOYA ConBio, Fremont, California) irradiation at fluences of 3.6, 4.2, 4.9, 6.3, 8.1 or 9.7 J cm at 20 or 30 Hz for 20 or 30 seconds on primary human gingival fibroblasts (HGFs). Irradiation at 6.3 J cm promoted maximal cell proliferation, determined by WST-8 assay and crystal violet staining, but was accompanied by lactate dehydrogenase release, on day 3 post-irradiation. Elevation of ATP level, Ki67 staining, and cyclin-A2 mRNA express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 36 publications
(52 reference statements)
4
25
2
Order By: Relevance
“…It is conceivable that the disparities in results are caused by differences in irradiation conditions (pulse energy and time) and/or cells used. In addition, although we previously reported that Er:YAG irradiation at 6.3 J/cm 2 promoted cell proliferation of human gingival fibroblasts, surface temperatures increased to 40.9 • C with upregulating genes of heat shock protein family proteins (Kong et al, 2018). The difference in temperature may also affect proliferation.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…It is conceivable that the disparities in results are caused by differences in irradiation conditions (pulse energy and time) and/or cells used. In addition, although we previously reported that Er:YAG irradiation at 6.3 J/cm 2 promoted cell proliferation of human gingival fibroblasts, surface temperatures increased to 40.9 • C with upregulating genes of heat shock protein family proteins (Kong et al, 2018). The difference in temperature may also affect proliferation.…”
Section: Discussionmentioning
confidence: 89%
“…We also evaluated cell proliferation using the Cell Counting Kit-8 (CCK-8, Dojindo, Kumamoto, Japan) at 1, 2, and 3 days after laser irradiation as described previously (Aleksic et al, 2010;Kong et al, 2018). Laser irradiation was performed in the absence of medium after a 24 h-starvation.…”
Section: Evaluation Of Cell Proliferationmentioning
confidence: 99%
“…Effect of laser irradiation on cell cycle and proliferation is reported by several researchers. 16,17 It seems that microtubule destabilization is a significant process that is affected by laser irradiation. Down-regulation of TP53 and activation of this anti-tumor protein indicates that control of cell proliferation after laser irradiation is a prominent point regarding using laser therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Laser irradiation was performed perpendicularly to the bottom of the culture dish at a distance of 25 cm, with the handpiece fixed using a stand as performed previously. 21,22 Neither cover sleeve nor contact tip mounting was used with the handpiece to completely irradiate the 35-mm dish and cover more than the dish area. The medium was removed immediately before irradiation, and all irradiations were performed in the absence of culture medium.…”
Section: Cell Isolation and Er:yag Laser Irradiationmentioning
confidence: 99%